Kidney transplantation and withdrawal rates among wait-listed first-generation immigrants in Italy. (5th April 2022) - Grossi, Alessandra Agnese; Puoti, Francesca; Fiaschetti, Pamela; Di Ciaccio, Paola; Maggiore, Umberto; Cardillo, Massimo
Abstract: Background: Multiple barriers diminish access to kidney transplantation (KT) in immigrant compared to non-immigrant populations. It is unknown whether immigration status reduces the likelihood of KT after wait-listing despite universal healthcare coverage with uniform access to transplantation. Methods: We retrospectively collected data of all adult waiting list (WL) registrants in Italy (2010–20) followed for 5 years until death, KT in a foreign center, deceased-donor kidney transplant (DDKT), living-donor kidney transplant (LDKT) or permanent withdrawal from the WL. We calculated adjusted relative probability of DDKT, LDKT and permanent WL withdrawal in different immigrant categories using competing-risks multiple regression models. Results: Patients were European Union (EU)-born ( n = 21 624), Eastern European-born ( n = 606) and non-European-born ( n = 1944). After controlling for age, sex, blood type, dialysis vintage, case-mix and sensitization status, non-European-born patients had lower LDKT rates compared to other immigrant categories: LDKT adjusted relative probability of non-European-born vs. Eastern European-born 0.51 (95% CI: 0.33–0.79; P = 0.002); of non-European-born vs. EU-Born: 0.65 (95% CI: 0.47–0.82; P = 0.001). Immigration status did not affect the rate of DDKT or permanent WL withdrawal. Conclusions: Among EU WL registrants, non-European immigration background is associated with reduced likelihood of LDKT but similar likelihood of DDKT and permanent WL withdrawal. Wherever not available, new national policies should enable coverage of travel and medical fees for living-donor surgery and follow-up for non-resident donors to improve uptake of LDKT in immigrant patients, and provide KT education that is culturally competent, individually tailored and easily understandable for patients and their potential living donors.